2015
DOI: 10.1353/hpu.2015.0092
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of the New WIC Food Package on Low-Fat Milk Consumption Among WIC Recipients: A Pilot Study

Abstract: Policy changes for WIC vouchers were implemented to encourage mothers to reduce fat calories in dairy products for them and their children. This represents a powerful, low-resource intervention to change health behaviors among low-income families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A longitudinal study of African–American and Hispanic women from WIC clinics in Chicago (n=273) found significant dietary improvements for Hispanic mothers who reported consuming more fruit, more reduced fat milk less whole milk and less saturated fat (all p<0.05). 39 African–American mothers reported consuming less whole milk (p=0.02) but no other changes were statistically significant. 41 There were no sustained dietary improvements in either group compared with baseline at 18 months.…”
Section: Resultsmentioning
confidence: 91%
“…A longitudinal study of African–American and Hispanic women from WIC clinics in Chicago (n=273) found significant dietary improvements for Hispanic mothers who reported consuming more fruit, more reduced fat milk less whole milk and less saturated fat (all p<0.05). 39 African–American mothers reported consuming less whole milk (p=0.02) but no other changes were statistically significant. 41 There were no sustained dietary improvements in either group compared with baseline at 18 months.…”
Section: Resultsmentioning
confidence: 91%
“…Forty-four studies assessed the association between the 2009 WIC food package revisions and availability of foods and beverages in supermarkets; purchases, redemptions, or dietary intake among WIC participants; obesity in early childhood; perinatal and birth outcomes; or outcomes related to breastfeeding [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. There is consistent evidence of an association between the WIC food package revisions and improvements in household food purchases and dietary intake among both adults and children [ 111 , 114 , 115 , 116 ...…”
Section: Resultsmentioning
confidence: 99%
“…Forty-four studies assessed the association between the 2009 WIC food package revisions and availability of foods and beverages in supermarkets; purchases, redemptions, or dietary intake among WIC participants; obesity in early childhood; perinatal and birth outcomes; or outcomes related to breastfeeding . There is consistent evidence of an association between the WIC food package revisions and improvements in household food purchases and dietary intake among both adults and children [111,[114][115][116]119,121,[135][136][137][138][139][140]145,[147][148][149]151]. Specifically, revisions to the food package are associated with improvements in total diet quality, increases in fruit, vegetables, whole grains, dietary fiber, and low-fat dairy, and reductions in full-fat dairy, saturated fat, and juice (with no evidence of complete substitution to other sugary drinks).…”
Section: Revise Composition and Quantities Of Foods Provided Through The Usda Special Supplemental Nutrition Program For Women Infants Anmentioning
confidence: 99%